Radiofrequency Catheter Ablation of Left Free Wall Accessory Pathways: Comparison Between Retrograde and Transeptal Approach - Hashem, S; Hossain, M; Ali, MA; Choudhury, AK; Masum, AA (Cardiovascular Journal, 2012)
Background : This study was conducted to compare the conventional retrograde arterial approach (RAA) with the transeptal approach (TSA) for radiofrequency catheter ablation (RFA) of left accessory pathways (AP). Materials and Methods: Sixty consecutive patients (44 male; mean age of 35.60 ± 11.63 years) with 60 left APs (39 overt and 21 concealed) underwent catheter ablation using the TS method (30 patients) and the RA method (30 patients) in an alternate fashion. The analysis was performed according to the intention-to-treat principle. Results : The transeptal puncture was successfully performed in 29 patients (96%). This access allowed primary success in the ablation in all the patients without any complication. When we compared this approach with the RAA there was no difference as regards the primary success (p = 0.103), fluoroscopy time (p = 0.565) and total time (p = 0.1917). Three patient in the RAA group presented a vascular complication. The TSA allowed shorter ablation times (p=0.006) and smaller number of radiofrequency applications (p = 0.042) as compared to the conventional RAA. The patients who had unsuccessful ablation in the first session in each approach underwent with the opposite technique (cross-over), with a final ablation success rate of 100%. Conclusion : The TS and RA approaches showed similar efficacy and safety for the ablation of left accessory pathways. The TSA allowed shorter ablation times and smaller number of radiofrequency applications. When the techniques were used in a complementary fashion, they increased the final efficacy of the ablation DOI: http://dx.doi.org/10.3329/cardio.v4i2.10458 Cardiovasc. j. 2012; 4(2): 139-147